Analisis Efektivitas Kebijakan Insentif Pph Pasal 21 Dalam Meningkatkan Penerimaan PPh Pasal 21 Pada Kantor Pelayanan Pajak Pratama Jakarta Kebon Jeruk Satu Tahun 2020 - Fauziah Dwi Kartika; Chairil Anwar Pohan (Jurnal Ilmu Administrasi Publik, 2021)
The purpose of this study is to analyze the effectiveness of the Article 21 PPh tax incentive policy in increasing Article 21 Income Tax revenue at the Jakarta Kebon Jeruk One Tax Service Office in 2020. The main problem in this study is how the level of effectiveness of the tax incentive activities is. This research approach uses a qualitative descriptive approach with data collection techniques in the form of interviews, observation, documentation, and triangulation. Based on the results of this study, when viewed from the effectiveness of tax incentives on tax revenues before and after tax incentives in 2020, it is classified as effective with an average effectiveness percentage of 96%. In addition, knowledge of taxation regarding compliance and level of awareness of taxpayers, as well as socialization has a significant positive effect on the Article 21 PPh tax incentive policy in Article 21 income tax revenue as well as mediates the analysis of the effectiveness of Article 21 PPh tax incentive policy in increasing Article 21 income tax revenue. 2020.